Semantic polysemy and psycholinguistics. (27th January 2021) - Devitt, Michael
Abstract : The paper urges that polysemous phenomena are typically semantic not pragmatic. The part of a message sent by a polysemous expression is typically one of its meanings encoded in the speaker's language and not the result of pragmatic modification. The hearer receives that part of the message by a process of disambiguation, by detecting which item in the lexicon the speaker has selected. This is the best explanation of observed regularities. The paper argues that the experimental evidence from psycholinguistics, particularly that produced in discussions of "underspecification" and "overspecification, " does not undermine this view nor support the pragmatic alternative.